Design and synthesis of conformationally constrained hydroxylated 4-phenyl-2-aryl chromenopyridines as novel and selective topoisomerase II-targeted antiproliferative agents. Issue 19 (1st October 2015) - Thapa, Pritam; Jun, Kyu-Yeon; Kadayat, Tara Man; Park, Chanmi; Zheng, Zhi; Thapa Magar, Til Bahadur; Bist, Ganesh; Shrestha, Aarajana; Na, Younghwa; Kwon, Youngjoo; Lee, Eung-Seok
Graphical abstract: A series of new conformationally constrained hydroxylated 4-phenyl-2-aryl chromenopyridines were designed and synthesized as selective topoisomerase II-targeted antiproliferative agents. Abstract: To develop novel selective topoisomerase II inhibitors, we designed and synthesized a series of conformationally constrained hydroxylated 4-phenyl-2-aryl chromenopyridines and evaluated their topoisomerase inhibitory activity and cytotoxicity against three human cancer cell lines (DU145, HCT15, and T47D) and a normal cell line (MCF10A). All of the prepared compounds displayed stronger or similar topoisomerase II inhibitory activity as well as cytotoxicity against three human cancer cell lines compared to etoposide. Compounds10a, 10g, 11a, 11f, 11g, 12a, 12f, and12g especially showed stronger topoisomerase II inhibitory activity as compared to etoposide at both 100 μM and 20 μM. A structure–activity relationship study revealed that hydroxyphenyl moiety at 4-position of pyridine and ortho -hydroxyphenyl or thienyl moiety at 2-position of pyridine has an important role in displaying selective topoisomerase II inhibition. The compound12b with para -hydroxyphenyl and meta -hydroxyphenyl at 4- and 2-position of pyridine, respectively, showed the most significant cytotoxicity against all three cancer cell lines, whereas less cytotoxicity to a normal cell line as compared to adriamycin.